Pentingnya menjalankan sholat 5 waktu secara berjama’ah daripada munfarid - Pradansa, Satria Yudha (Maliki Interdisciplinary Journal, 2024)
Prayer is one of the important acts of worship in Islam that plays a central role in the lives of Muslims. Prayer is divided into two categories, obligatory prayers and voluntary prayers. The obligatory prayers, commonly known as the five daily prayers, are a duty for Muslims. Prayer is not just a personal obligation, it also becomes a collective duty to remind one another. The five daily prayers can be performed individually or in congregation. However, when performed in congregation, they carry a profound significance and virtue. Through congregational prayers, individuals experience closeness to Allah and have the opportunity to strengthen their relationships with fellow Muslims. Participating in congregational prayers comes with numerous virtues, including greater rewards compared to individual prayers and the fostering of solidarity among the Muslim community.